2002
DOI: 10.1007/s10350-004-6453-0
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Mapping for Colorectal Cancer With Radioactive Tracer

Abstract: Intraoperative radioactivity-guided sentinel node mapping was accurate for patients with colorectal cancer with T1 or T2 tumors. The results suggest that sentinel node mapping and intraoperative biopsy may be a sensitive and specific diagnostic method for detecting metastasis in regional lymph nodes in patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
16

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 22 publications
2
42
0
16
Order By: Relevance
“…Large prospective trials using a combination of blue dye and radiocolloid, such as used in SLN mapping for breast cancer and melanoma, may reveal higher success rates of this technique in colon cancer. 49 Kitagawa et al 56 reported the only study to date that investigated the feasibility of SLN mapping using preoperative endoscopic injection of only technetiumlabeled tin colloid in patients with sigmoid colon and rectal cancer. Since only limited results are available regarding the feasibility and accuracy of radiocolloidguided SLN mapping in colon cancer, more studies should be performed in which the value of radiocolloid as a tracer is investigated.…”
Section: Figmentioning
confidence: 99%
“…Large prospective trials using a combination of blue dye and radiocolloid, such as used in SLN mapping for breast cancer and melanoma, may reveal higher success rates of this technique in colon cancer. 49 Kitagawa et al 56 reported the only study to date that investigated the feasibility of SLN mapping using preoperative endoscopic injection of only technetiumlabeled tin colloid in patients with sigmoid colon and rectal cancer. Since only limited results are available regarding the feasibility and accuracy of radiocolloidguided SLN mapping in colon cancer, more studies should be performed in which the value of radiocolloid as a tracer is investigated.…”
Section: Figmentioning
confidence: 99%
“…Four studies reported sentinel node biopsy using both blue dye and radioactive tracer [23,[26][27][28] and in two studies only radioactive tracer was used [18,29]. The moment of injection was usually in vivo and the site of injection was mostly subserosally and sometimes submucosally during an endoscopy or ex vivo procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of SLN found per patient ranges from 1.5 [10] to 3.5 [18]. The figures of upstaging (0-24%) vary considerably among studies [10,14,17,[19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Quando observados somente os trabalhos que utilizaram o método combinado (corante e radiofármaco), como nesta avaliação, a taxa média foi de 28%, variando de 0 a 50% 19,27,29 . De acordo com o estudo de validade deste trabalho, a sensibilidade foi 66,7%, enquanto na literatura varia de 40 a 100% 17,26,28 . Há um consenso que quanto mais avançado for o tumor, mais alto deverá ser o índice de falsonegativo e menor a sensibilidade.…”
Section: Falso-negativo E Sensibilidadeunclassified